Influence of thiourea synthesis with silica fume on the corrosion rate of reinforcement concrete. Issue 3 (3rd May 2020) - Tawfik, Taher A.; El-Yamani, Magdy A.; Serag Faried, A.; Mohammed, Shimaa M.; AbdEl-Hafez, Gh.M.
ABSTRACT: The examination of corrosion rate for steel reinforcement existent in concrete was carried out in the presence of silica fume and thiourea. The ordinary Portland cement (OPC) replacement was conducted with silica fume material at 5 and 10% by cement weight for concrete production, in addition to that using various percentage of thiourea (1, 2, 3 4 and 5%) added to concrete. Monitoring and estimating the corrosion rate for reinforcing steel existent in concrete with and without silica fume and thiourea was held with the usage of corrosion test cell. Besides, compressive and splitting tensile strength submerged in fresh and salty water of hardened concrete with and without silica fume and thiourea that were considered in the study. The immersion for all the samples of steel reinforcement with salty water (tap water with 1.5% of calcium sulphate and 3% of sodium chloride) for about 90 days of exposure were studied. The best results for the lowest corrosion rate were obtained when a mixture of silica fume with thiourea is used with concentrations of 10 and 3%, respectively compared with the ordinary concrete.